1975
DOI: 10.1111/j.1469-7998.1975.tb01411.x
|View full text |Cite
|
Sign up to set email alerts
|

Foods and foraging places of rats (Rodentia: Muridae) in the lowland evergreen forest of Ghana

Abstract: A study was made of the foods and ground-zone foraging places of Muridae in littledisturbed moist evergreen forest in Ghana, West Africa. Data were obtained by means of baited traps operated for about SO00 trap-nights, and by the examination of the contents of 218 stomachs.Seven species of rats were found, of which six are believed to be members of the natural forest fauna. Foraging places of rats of some species were found to be related to features of the topography and the structure of the vegetation. Diets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Similarly, most studies of terrestrial small mammals in West African forests found P. tullbergi to be the dominant species. For example, in western Ghana, Cole (1975) and Jeffrey (1977) recorded P. tullbergi as the most dominant rodent in a lowland evergreen forest and primary forest, new farms and cocoa plantations. The same was reported for some Nigerian forests (Iyawe, 1989;Oguge, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, most studies of terrestrial small mammals in West African forests found P. tullbergi to be the dominant species. For example, in western Ghana, Cole (1975) and Jeffrey (1977) recorded P. tullbergi as the most dominant rodent in a lowland evergreen forest and primary forest, new farms and cocoa plantations. The same was reported for some Nigerian forests (Iyawe, 1989;Oguge, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…(Decher and Bahian, 1999). Most small mammal studies in forests in Ghana have reported P. tullbergi as the dominant species (Cole, 1975;Jeffrey, 1977;Ofori et al, 2013b). In this study however, H. alleni was the most abundant forest-specialist species, even though the numerical difference in individual numbers between these species was not as large as their relative abundance scores might suggest.…”
Section: Relative Abundance Diversity and Compositionmentioning
confidence: 99%
“…Our current understanding of the habitat preferences of rodents and insectivores in Africa is weak because studies have been conducted in different ecosystems, each with different study objectives, methodologies and lengths of study periods (e.g. Delany, 1971; Cole, 1975; Cheeseman & Delany, 1979; Iwaye, 1989; Stephenson, 1993; Sillero‐Zubiri, Tattersall & Macdonald, 1995; Keesing, 1998; Granjon et al. , 2002).…”
Section: Introductionmentioning
confidence: 99%